Cross-national heterogeneity in e-retail spending: a longitudinal analysis of economic, technological and political forces - Bebenroth, Ralf (2015)
This paper examines the technological, market, industry and institutional sources associated with the cross-national heterogeneity in e-retail spending. We used the economic theory of complementarities as the theoretical framework and estimated panel data models for 10 year data from 43 countries to test our hypotheses. We identified various activities and resources in the e-retail ecosystems that may produce positive or negative externalities in the development of the e-retail industry. We found that broadband Internet is an important determinant of an economy’s e-readiness in explaining international heterogeneity in e-retail spending. We also found various specific attributes of the traditional retail environment that produce enhancing effects as well as suppressing effects for e-retail spending.